Lombok, Indonesia Earthquake: What Happened and Why? - Harun, Hasnida; A. Hamid, Hazren; Sunar, N.M.; Ahmad, Faridahanim (Penerbit UTHM, 2020)
Earthquake can occur when any sudden shaking of the ground that can cause by the passage of seismic waves through Earth’s rocks. Earthquakes occur most often along geologic faults, narrow zones where rock masses move in relation to one another. The vital fault lines of the world are located at the fringes of the huge tectonic plates that make up Earth’s crust [1]. Seismic wave is a vibration that created by an earthquake, explosion, or similar energetic source and propagated within the Earth or along its surface [2]. Seismic waves can produced when some form of energy stored in Earth’s crust is suddenly released, usually when masses of rock straining against one another suddenly fracture and “slip” [1].